2008
DOI: 10.1051/0004-6361:200809783
|View full text |Cite
|
Sign up to set email alerts
|

Galaxies with Wolf-Rayet signatures in the low-redshift Universe

Abstract: Context. The availability of large spectroscopic datasets has opened up the possibility of constructing large samples of rare objects in a systematic manner. Aims. The goal of this study is to analyse the properties of galaxies showing Wolf-Rayet features in their optical spectrum using spectra from the Sloan Digital Sky Survey Release 6. With this unprecedentedly large sample we aim to constrain the properties of the Wolf-Rayet phase and its impact on the surrounding interstellar medium. Methods. We carried o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
284
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(315 citation statements)
references
References 108 publications
25
284
6
Order By: Relevance
“…There are two main WR features (see e.g. Brinchmann et al 2008) seen in optical spectra: the blue (4600-4680 Å) and red (5650-5800 Å) bumps. However, we do not find these features in our spectra for components A, B, or C. We followed the method used in Thöne et al (2015) to determine the upper limit of WR star populations.…”
Section: Interacting Galaxy Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main WR features (see e.g. Brinchmann et al 2008) seen in optical spectra: the blue (4600-4680 Å) and red (5650-5800 Å) bumps. However, we do not find these features in our spectra for components A, B, or C. We followed the method used in Thöne et al (2015) to determine the upper limit of WR star populations.…”
Section: Interacting Galaxy Systemmentioning
confidence: 99%
“…However, we do not find these features in our spectra for components A, B, or C. We followed the method used in Thöne et al (2015) to determine the upper limit of WR star populations. We measured the 3σ detection limit of He ii λ4686 and C IV λ5808 lines assuming a full width at half maximum (FWHM) between 1000 and 3000 km s −1 (Brinchmann et al 2008). The luminosity of He ii line is < 9.29 × 10 38 -2.80 × 10 39 erg s −1 , and that of C IV line is < 1.29 × 10 39 -3.86×10 39 erg s −1 .…”
Section: Interacting Galaxy Systemmentioning
confidence: 99%
“…The very rare occurrence of objects with a large N overabundance suggests the general idea of the short-time scales for the localized N pollution and its fast dispersal. Brinchmann et al (2008) used SDSS data to find that for |W(Hβ)| ≥ 100 Å, WR galaxies show a high N/O compared to non-WR galaxies. Quantitatively these authors found that on average Δ log(N/O) [ features, which likely is a reflection of WR stars being more abundant at higher metallicities (see Fig.…”
Section: Nitrogen Enrichment In Wr Galaxiesmentioning
confidence: 99%
“…Although we do not dismiss the statistical analysis performed by Brinchmann et al (2008) comparing WR and non-WR galaxy data, we would like to warn about the use of data with low spectral resolution in order to derive an accurate nitrogen abundance in individual objects. This is commonly done via the analysis of the [N ii] λ5683 emission line, very close to Hα.…”
Section: Nitrogen Enrichment In Wr Galaxiesmentioning
confidence: 99%
“…Outside the Local Group, Brinchmann et al (2008) analysed spectra of 570 WR galaxies from SDSS6 and conclude that at 12 + log O/H < 8.0, the main sources of HeII ionizing photons appears to be O stars, arguing for a less dense stellar wind at these metallicities, while at higher abundances WN stars might increasingly dominate the ionization budget. De Mello et al (1998) showed that the observed equivalent widths of nebular HeII λ 4686 emission in the BCD IZw18 can be reproduced from an instantaneous burst model with the present WC/WO stars.…”
Section: Introductionmentioning
confidence: 99%